Penyesuaian Sosial Siswa Akselerasi Ditinjau Dari Konsep Diri dan Membuka Diri - Tri Rejeki Andayani (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
The aims of this research is to find out relationship between self-concept and self-disclosure with the social adjustment of them. This study population were 89 students of Class X and XI in the High School (SMAN 3 Surakarta). Collecting data use three scales: 1) Self-concept Scale, the validity of items ranged between 0,259-0,658, the reliability is 0.848; 2) Self-disclosure Scale, the validity of items ranged between 0,280-0,694, reliability is 0.872; and 3) Social Adjustment Scale, the validity of the items between 0,284-0,646, the reliability is 0.821. Analysis data in this study is using multiple regression analysis technique. The results of multiple regression analysis revealed a significant relationship between selfconcept and self-disclosure with social adjustment of students with acceleration. Student who have a positive self-concept and accept themselves more positively will be open in accepting criticism and inprove ourselves, so that tends to adapt better. Positive self-concept of accelleration means that students have a positive outlook on his ability and circumstances, giving rise to the confidence to bring him to the wider social environtment. However, the student who have negative self-concept will be developed feelings of inadequacy, low self-esteem and tend to carry themselves in difficult social adjustment.Â ABSTRAKÂ Penelitian ini bertujuan untuk mengetahui hubungan antara konsep diri dan membuka diri dengan penyesuaian sosial siswa akselerasi. Populasi penelitian sebanyak 89 siswa, terdiri atas siswa Akselerasi Kelas X dan XI SMAN 3 Surakarta. Pengumpulan data mengunakan tiga buah skala, yakni : 1) Skala Konsep Diri, validitas item berkisar antara 0,259-0,658, reliabilitas alat ukur 0,848; 2) Skala Membuka Diri, validitas item 0,280-0,694, reliabilitas alat ukur 0,872; dan 3) Skala Penyesuaian Sosial, validitas item 0,284-0,646, reliabilitas alat ukur 0,821. Analisis data menggunakan Teknik Analisis Regresi Ganda. Hasil analisis data menunjukkan bahwa ada hubungan antara konsep diri dan membuka diri dengan penyesuaian sosial siswa akselerasi. Siswa yang memiliki pandangan positif dan menerima diri secara positif akan lebih bersikap terbuka dalam menerima kritik dan memperbaiki diri. Konsep diri yang positif berarti siswa akselerasi memiliki pandangan positif terhadap kemampuan dan keadaan dirinya, sehingga menimbulkan rasa percaya diri untuk membawa dirinya pada lingkungan pergaulan yang lebih luas. Sebaliknya, siswa yang memiliki konsep diri negatif akan mengembangkan perasaan tidak mampu, rendah diri dan cenderung sulit membawa diri pada lingkungan pergaulan yang lebih luas.